PENGEMBANGAN STRATEGI PEMBELAJARAN DAN PEMILIHAN BAHAN AJAR - Zain, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2017)
Abstract: To create a superior learning process / quality, it is necessary to develop a special strategy that makes students motivated to learn and always feel the pleasure in learning. In developing such learning strategies, students become the center of attention. criteria that must be met in the learning model or the development of learning are: 1) have a purpose; 2) harmony with purpose; 3) systematic; 4) having evaluation activities; and 5) fun. Therefore, the learning system can be likened to a production process consisting of an input-process-output part, which is mutually integrated. All professionals must have professional skills in their fields, among others, to make designs about things to do. So the problem is that the work works well. Ability to develop techniques in learning because all teachers want the results of education work well. Moreover, he is not dealing with inanimate objects, but a growing human child and developing.